The Winner's Curse and Public Information in Common Value Auctions: Comment - Cox, James C; Dinkin, Samuel H; Smith, Vernon L (American Economic Review, 1999)
The Winner's Curse and Public Information in Common Value Auctions: Comment by James C. Cox, Samuel H. Dinkin and Vernon L. Smith. Published in volume 89, issue 1, pages 319-324 of American Economic Review, March 1999